Does Organizational Commitment to Mental Health Affect Team Processes? A Longitudinal Study - Volpi L; Giusino D; Pietrantoni L; De Angelis M (Dove Medical Press, 2023)
Lucia Volpi, Davide Giusino, Luca Pietrantoni, Marco De Angelis Department of Psychology, University of Bologna, Bologna, ItalyCorrespondence: Marco De Angelis, Viale Berti Pichat, 5 40127, Bologna, Italy, Tel +39 3288967582, Email marco.deangelis6@unibo.itPurpose: Team processes, such as reflexivity and participation, are critical for organizational sustainability, especially in high-reliability professions such as healthcare. However, little is known about health-related predictors of team processes. Basing our hypotheses on the Input-Process-Output (IPO) model, this study investigates the influence of perceived organizational commitment to mental health (OCMH) on healthcare workers' team reflexivity and participation via mental health-specific leadership (MHsL) and team autonomy.Patients and Methods: The study involved 82 participants (ie, physicians, nurses, healthcare assistants, healthcare technicians, and physiotherapists) working in the Medicine, Emergency, and Neurological Departments at a large public healthcare organization in Italy. Data was gathered at 2-time points, 14 months apart.Results: The results suggest that healthcare workers' perception of their organization's support for mental health at T1 significantly impacts team participation at T2 through MHsL and team autonomy. Likewise, the indirect effect of OCMH through MHsL and team autonomy was also significant in the model predicting team reflexivity. However, in both models, no direct relationship of OCMH on the dependent variables was found.Conclusion: The findings highlight the importance of a mental health-supportive environment and leadership to foster team autonomy and, subsequentially, team processes, which are fundamental for performance and patient care.Keywords: mental health-oriented leadership, team autonomy, team reflexivity, team participation, healthcare, workplace mental health